Estilo de afrontamiento de un adulto de 62 años con diagnóstico de enfermedad catastrófica - Fajardo Viejo, Yelena Maite (2021)
This case study focused on identifying the coping process of an adult over 62 years of age with catastrophic illness, in which we proceeded to analyze personal, family and work factors, which have been affected by the given health environment Because the disease presented by the person under study is kidney disease for which they must attend hemodialysis treatment every three weeks. Based on the problem presented in conjunction with other previous comorbidities, it was possible to identify that the coping presented by the patient is extrinsic in nature, given that their motivation is their family, who have kept an eye on the patient in all the necessary care. In this case study, a 4-session approach was carried out and the Yesavage Geriatric Depression Scale was applied, in which it was identified that the patient gave more importance to the things that he had lost, in that he referred to his amputations. his lower limbs caused by diabetes and kidney disease that has no cure, to the things he had acquired such as a family since the patient never married or had children, in which he is actively living with his brother, sister-in-law and nephews. Therefore, a psychotherapeutic plan was established with a cognitive-behavioral approach which would allow reflection on their type of coping in order to modify thoughts and cognitive distortions.